Assessment of KOH-activated unripe Musa paradisiaca peel for adsorption of copper from aqueous solution. Issue 1 (1st January 2017) - Emenike, PraiseGod Chidozie; Omole, David Olugbenga; Ngene, Ben Uche; Tenebe, Imokhai Theophilus
Abstract: Adsorption of copper ions out of aqueous solution by preparing activated carbon from unripe Musa paradisiaca peel (U mp P) with KOH was investigated. Estimation of the adsorption constants was achieved by adopting the Langmuir and Freundlich models. Results revealed that the adsorption process was fast and equilibrium was reached at 55 mins. The adsorption efficiency was highly influenced by the pH of the solution, and the maximum adsorption was attained at pH 7.5. In addition, an increase in adsorption capacity was observed with increase in contact time and initial copper concentration. The adsorption process was explained by both Langmuir and Freundlich models having R 2 value of 0.9977 and 0.9959 at 303 K respectively and R 2 value of 0.9922 and 0.9904 at 308 K respectively. The maximum adsorption capacity of KOH-modified U mp P at the specified conditions was found to be 9.980 and 9.766 mg/g at 303 and 308 K respectively. Sequel to modelling the kinetic data, the Pseudo-second-order model gave the best fit with R 2  = 0.9990 and 0.9977 at 303 and 308 K respectively, indicating that the adsorption process is restricted to chemisorption. KOH-modified U mp P can serve as an economically and environmentally viable sorbent for the removal of copper from contaminated waters.